A Sero-Epidemiological Study on Visceral Leishmaniasis among Volunteer Children and Adults in Rural Areas of Shahroud, Iran 2018-2019 - Sajjad Ghodrati; Behnaz Akhoundi; Mehdi Mohebali; Mohammad Zeinali; Homa Hajjaran; Zahra Kakooei (Tehran University of Medical Sciences, 2023)
Background: Visceral leishmaniasis (VL) also known as Kala-azar is considered as one of the zoonotic infections in Mediterranean countries. The reservoir of this infection is dogs and sand flies are considered as its vectors. Due to reported sporadic cases of Kala-azar in the past five years in Shahroud County, Semnan Province, Iran, this study aimed to investigate the status of this infection in this area and to determine its seroepidemiology to take required measurements for infection control and treatment. Methods: This descriptive cross-sectional study was conducted on 504 subjects residing in seven villages in Shahroud County, Semnan, Iran. Samples were randomly selected using the cluster sampling method and blood samples were collected from subjects aged up to 13 years old (90%) and adults over 13 years old (10%) from September 2018 to May 2019. After separating sera from whole blood, samples were subjected to direct agglutination test (DAT) to detect anti-Leishmania infantum antibodies. First dilutions were prepared from 1:10 to 1:800 for human samples. Results: Results of serological testing with 1:800 titration indicated that no sample was positive for antibody against Leishmania infantum. After secondary screening, 10 cases (1.98%) showed the antibody titer of 1:100, while four cases (0.79%) showed the antibody titer of 1:400. According to clinical findings, no patient was suffering from fever, weight loss, splenomegaly, hepatomegaly, and cachexia and therefore did not show the symptoms of Kala-azar. Conclusion: The results of the current study indicate that Kala-azar is not prevalent in Shahroud County.